Seismic assessment of low ductile RC structures: Buildings from before the modern seismic codes - João Dias Oliveira (2016)
Purpose - When a numerous amount of buildings was built in reinforced concrete, in a period whenthe regulations did not have the design philosophy for the occurrence of earthquakes, it is of extremeimportance to carry out full and effective structural assessments, specially considering and comparingbare frame and infilled structure. The paper aims to discuss these issues.Design/methodology/approach - Among several possibilities to make the evaluation as, simplified,linear analysis and static non-linear analysis, the non-linear dynamic can provide the most accuratenumerical behaviour compared to the real one. The time-history non-linear analyses are developed onthe software SeismoStruct for different levels of intensity. Local verifications are then appliedseparately from both Eurocode and Italian Code.Findings - The application of validated models for the analysis of real buildings allows a completeseismic assessment. The level of uncertainty increases integrating particularities regarding the infillmasonry walls. The paper shows important global and local seismic safety for these complex typologyof buildings.Originality/value - A representative common concrete structure without seismic provisions is firstanalysed and discussed in terms of global behaviour, deformations and progression of forces. The casestudy structure is considered both as bare structure and with integrated infill panels. It is alsodiscussed in a local level, about brittle and ductile mechanisms, and extra comparisons betweendifferent interpretations of different standards. The case study structure is considered both as barestructure and with integrated infill panels.Keywords 3D modelling, Dynamic and non-linear analysis, Infill masonry, RC building,Seismic assessmentPaper type Case study